Note on a Promising Green Manure Plant of the Rainfed Tracts: Mundulea suberosa (Benth.) - Chinnamani, S.; Bhaskaran, A. R. (Indian Forester, 1969)
Protection and utilisation of barren, eroded semi-arid patches of land, fields and contour bunds is made possible by the use of Mundulea suberosa (Benth.) which has proved itself as a good fodder and green manure plant capable of growing under the above exacting conditions. Improvement for the fodder and nitrogen production of this plant by clonal selection is suggested.